Placebo response in trichotillomania - Grant, JE; Chamberlain, SR; Redden, SA; Odlaug, BL; van Ameringen, M; Dougherty, DD; Keuthen, NJ; Kim, SW (Wolters Kluwer Health, 2017)
Background: Trichotillomania is a functionally impairing, often overlooked disorder with no FDA-approved medications indicated for its treatment. The ability of clinical trials to detect beneficial effects of pharmacologic treatment in trichotillomania has been hampered by the high placebo response rate. Very little is known about baseline demographic and clinical characteristics that may be predictive of placebo response in such patients. Methods: 104 participants assigned to placebo were pooled from five double-blind trials conducted at three sites in the United States and Canada. Participants were classified as placebo responders or non-responders based on a cut-off of 35% reduction in symptom severity on the Massachusetts General Hospital Hair Pulling Scale (MGH-HPS). Baseline group differences were characterized using t-tests and equivalent non-parametric tests as appropriate. Results: Thirty-one percent of individuals assigned to placebo treatment showed a significant clinical response to placebo. Placebo responders (n=32) and non-responders (n=72) did not differ significantly on any demographic or clinical variable. Discussion: Predictors of placebo response for trichotillomania remain elusive and do not appear similar to those reported for other mental health disorders.
Keywords: Adult; Canada; Double-Blind Method; Female; Humans; Male; Placebo Effect; Single-Blind Method; Treatment Outcome; Trichotillomania; United States; Young Adult